2015
DOI: 10.1111/tpj.12819
|View full text |Cite
|
Sign up to set email alerts
|

OsNAC2 encoding a NAC transcription factor that affects plant height through mediating the gibberellic acid pathway in rice

Abstract: These authors contributed equally to the work. SUMMARYPlant height and flowering time are key agronomic traits affecting yield in rice (Oryza sativa). In this study, we investigated the functions in rice growth and development of OsNAC2, encoding a NAC transcription factor in rice. Transgenic plants that constitutively expressed OsNAC2 had shorter internodes, shorter spikelets, and were more insensitive to gibberellic acid (GA 3 ). In addition, the levels of GAs decreased in OsNAC2 overexpression plants, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 55 publications
6
88
0
Order By: Relevance
“…4 and 7). Similarly, Chen et al (2015) reported that OsNAC2 repressed the expression of GA biosynthetic genes, OsKO2, and enhanced the expression of OsEATB, which encodes a repressor of GA biosynthesis (Chen et al, 2015). Additionally, MYC2, a basic helix-loop-helix domaincontaining TF, acts as both activator and repressor to modulate the expression jasmonic acid-responsive genes in Arabidopsis (Dombrecht et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…4 and 7). Similarly, Chen et al (2015) reported that OsNAC2 repressed the expression of GA biosynthetic genes, OsKO2, and enhanced the expression of OsEATB, which encodes a repressor of GA biosynthesis (Chen et al, 2015). Additionally, MYC2, a basic helix-loop-helix domaincontaining TF, acts as both activator and repressor to modulate the expression jasmonic acid-responsive genes in Arabidopsis (Dombrecht et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…To study the role of OsNAC2 in leaf senescence, we examined the senescence symptoms of transgenic lines, including 35S::OsNAC2 lines (OsNAC2-OX, ON7, and ON11) and knockdown lines (OsNAC2-RNAi18, RNAi25, and RNAi31), which were previously reported (Chen et al, 2015). The third leaves of 6-week-old seedlings hydroponically cultivated were used for statistics of yellowing rate.…”
Section: Osnac2 Is Highly Expressed During Leaf Senescence and Positimentioning
confidence: 99%
See 2 more Smart Citations
“…The list of genes involved in controlling rice plant height and their expression in overexpression transgenics is provided in Table I. The expression of some of them, including OsNAC2, OsGDD1, OsPIL1, and OsEATB, was checked Qi et al, 2011;Todaka et al, 2012;Chen et al, 2015). The expression of OsNAC2 was high, but OsPIL1, OsGDD1, and OsEATB were down-regulated in these transgenics (Fig.…”
Section: Osbzip48mentioning
confidence: 99%